Inflation Hedging Across Asset Classes: A Non-Linear Perspective from the South African Context - Tseeke, Rethabile (University of the Witwatersrand, Johannesburg, 2024)
Navigating the intricacies of financial markets, investors grapple with the enduring challenge of preserving portfolio value amidst the complexities of inflation. This study delves into the dynamic interplay between inflation and returns across diverse asset classes, focusing on the distinctive nuances within South Africa. Against the backdrop of global disruptions such as the Covid-19 pandemic and geopolitical tensions, the research examines the inflation-hedging potential within traditional and alternative investments, including the emergent domain of cryptocurrencies. Situated within the framework of the "Inflation targeting" strategy embraced by the South African Reserve Bank, the study employs the NARDL model, which rigorously tests the short and long-run relationships between the asset returns and inflation. The research imparts nuanced insights into the complex environment of inflation hedging in the South African market.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Commerce, Law and Management, School of Economics and Business Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; nflation Hedging; South African Context; SDG-8: Decent work and economic growth